Height Measurement System Based on Edge Detection Technique and Analysis of Digital Image Processing - Ida udlhiya (JAICT, 2017)
Height measurement is important in the field of health, athletics, and others. During this process the measurement height is done manually by using the tools in the form of tape measure or ruler. This takes quite a long time. With the weaknesses of such height measurements, then on this research designed a height measurement system based on Digital Image Processing Techniques. The parameters used for this research is the distance of the camera, the height of the camera, the camera angle, the color of the shirt, and the position of the object. Testing is done by performing processing and digital image analysis. By using these techniques, it only takes 35 seconds to process measurement and results. In addition to the test results can be stored in the system database, making it easier for data archiving. Of the overall testing with parameters of the camera distance, the height of the camera, the camera angle, the color of the shirt, and the position of the object, resulting in a measurement of the height of a more objective and accurate with the level of accuracy of 99.5%.